"Perrotta Integrative Clinical Interview (PICI-1)": Psychodiagnostic evidence and clinical profiles in relation to the MMPI-II - Giulio Perrotta (Annals of Psychiatry and Treatment - Peertechz Publications, 2020)
Purpose: In order to study in depth the paraphiliac universe of the patient, avoiding diagnostic errors in terms of sexuality, sexual fantasies and disorders codified by the DSM-V, this research work focused on the importance of the exact identification of relevant sexual behaviours, in order to facilitate the relationship with the patient and the therapeutic pathway.  Methods: Once the population sample had been selected, which met the required requirements (age between 18 and 65 years, confirmed psychopathological diagnosis, absence of degenerative neurological pathologies and ability to understand and want to participate in the research), the first practical phase of the research was carried out with the execution of the clinical interview, asking the participants to omit any information (at this stage) about the previous psychopathological diagnosis suffered, so as not to induce the writer into any conditioning. The second and third phases of the research concluded with the initialling and interpretation, in the telematic presence with the interviewed subject, of the PICI-1 clinical interview (TA version). The fourth and fifth phases of the research concluded with the initialling and interpretation, in the telematic presence with the interviewed subject, of the MMPI-II, detecting in particular the clinical and content scales, with a value higher than 65 points (correct). The last phase of the research, the sixth, ended with an informative comparison between the results of the MMPI-II test and those of the PICI-1TA clinical interview.  Results: With a population sample of 472 participants (240 males and 232 females), performing first a clinical interview, then the PICI-1TA and finally the MMPI-II, a comparison of 98.73% of the results was valid, while the remaining 1.27% seems to be attributable to circumstances that can be identified, such as the interpretative limits of the theoretical model of the MMPI-II, a psychodiagnostic error during the previous diagnosis and the psychopathological evolution of the previously identified disorder. For reasons of theoretical differences in the models, it is not possible to carry out the same analysis for the PICI-1 children's version (C), as the reference nosography also changes with respect to the DSM-V.  Conclusions: With this research, despite the insufficiently representative sample, the effectiveness, efficiency and psychodiagnostic reliability of the Perrotta Integrative Clinical Interview (PICI-1), version for adolescents and adults (TA), was demonstrated in relation to the evidence obtained by comparing the data with the Minnesota Multiphasic Personality Inventory (MMPI-II). In particular, some aspects not identified by the MMPI-II emerged in the PICI-1, extremely useful to better profile the patient and proceed in a more systematic way to the specific clinical treatment.